Penggunaan Model DRTA Berbantuan Media Big Book dalam Pembelajaran Membaca Pemahaman Siswa Kelas V SD Negeri 2 Kota Ternate - Hi. Karim, Kodrat; Husain, Siti Rohayati; Ahsan, Sukria (Universitas Khairun, 2024)
This research was conducted with the aim of finding out how DRTA is used and to describe the results in reading comprehension skills in class V students of Negeri 2 Ternate City. The research design is qualitative research that uses a descriptive approach. The instruments used are test questions, teacher and student observation sheets, and interview sheets. The data analysis technique used is the Miles and Huberman model analysis technique. The use of the DRTA learning model based on big book media is carried out as follows: (1) students predict the title as a guide in predicting the content of the reading text. (2) students predict the content of the reading based on the pictures they have seen. (3) researchers distribute big book media and students read the text in the first paragraph. (4) students assess and check the accuracy of predictions (5) the teacher repeats procedures 1 to 4 for each paragraph. (6) students make a summary, students write whatever information they understand in the reading text on the big book media. The results of using the DRTA learning model assisted by big book media are that in the indicator (1) determine the main idea there are 25% of students who answer with the right answer, in the indicator (2) answer questions according to the content of the text' there are 50% of students who answer with the right answer, in the indicator (3) rewriting the contents of the reading text there were 13% of students who answered with the right answer, and the indicator (4) making a summary there were 12% of students who could answer the question with the right answer. The conclusion is that based on the reading comprehension test results, class VB students at State Elementary School 2 Ternate City obtained an average score of 70.47 in the sufficient category.